Technocracy and non-partisanship of rights in Chile. The “statement” of Jorge Alessandri (1958-1964) (Tzintzun, Revista de Estudios Históricos, 2019)
The managerial technocracy had its first expression in Chile in the governmentof Jorge Alessandri Rodríguez, an eclectic liberal. Indeed, who ruledbetween 1958 and 1964 was characterized by a first phase of his governmentthat included Cabinet Managers, obeying various influences technocraticand depoliticizing against the traditional form of partisan political administration.
Keywords: History of Chile; Technocracy; State Administration; Right